Understanding Patient Compliance During Orthodontic Treatment - Snigdha Pattanaik (Institute of Medico-legal Publications Pvt Ltd, 2020)
The practice of orthodontics has sometimes been described as involving two distinct but related processes,the physiological-mechanical and the psychological-educational. Proper application of appliances to thephysiological-mechanical is essential to successful treatment, but no amount of attention by the orthodontistto sophisticated techniques is likely to have much effect, if those efforts are met with resistance or indifferenceon the part of the patient. But how does one counter that indifference or overcome that resistance? How doesone even understand it? This is a most serious and baffling problem, because it is very difficult for those inthe health professions to distinguish which patients will be compliant and which will not, and to know whatto do about it.